Toxicological evaluation of oral exposure to isoniazid: behavioral, biochemical, and histopathological assessments in rats. (2nd November 2022) - Ben Said, Dorra; Dahmani, Israa; Ben Ali, Ridha; Bassem, Hammami; El Fekih, Moncef; Chedly, Achraf; Elmay, Michelle-Véronique; Gaies, Emna; El Aidli, Sihem
Abstract: Isoniazid (INH), being the first-line drug used as an anti-tuberculosis drug, is known to be associated with physiological deteriorations including hepatic and neurologic disturbances. This study was aimed at biochemical and behavioral characterization of toxic manifestations of isoniazid treatment in Wistar rats. Experimental animals were divided into four groups. Each group consists of six animals including the control group (saline solution), I25 group (25 mg/kg of INH), I50 group (50 mg/kg of INH), and I100 group (100 mg/kg of INH). Animals received daily INH for 30 days. Isoniazid is known to be associated with hepatotoxicity; it's among the most common causes of drug-induced toxicities. For this reason assays for aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), and lactate dehydrogenase (LDH) were performed to assess liver toxicity. Moreover, behavioral study, renal, and lipid parameters were also assessed in addition to histological features of the liver and brain. Significant differences in all studied parameters were seen especially in the I100 group and a marked increase in liver enzymes activities, such as AST and ALT was observed. In another hand, there were no major clinical signs in treated animals, except fatigue and anxiety in the I100 group. On the other hand, the histological findings showed potential liver and brain injury which was evidenced by degenerative changes, infiltration, and hepatocyte necrosis, in addition to the appearance of many pyramidales cells in the gyrus. The current study findings suggest that INH interacts with multiple biochemical pathways in the body what comes up by behavioral changes and liver disturbances in animals caused by INH toxicity.